Epigenetics in Kawasaki Disease - Sharma, Kaushal; Vignesh, Pandiarajan; Srivastava, Priyanka; Sharma, Jyoti; Chaudhary, Himanshi; Mondal, Sanjib; Kaur, Anupriya; Kaur, Harvinder; Singh, Surjit (Frontiers in Pediatrics, 2021)
Kawasaki disease (KD) is a common febrile multisystemic inflammatory illness in children that preferentially affects coronary arteries. Children with KD who develop coronary artery aneurysms have a life-long risk of premature coronary artery disease. Hypothesis of inherent predisposition to KD is supported by epidemiological evidence that suggests increased risk of development of disease in certain ethnicities and in children with a previous history of KD in siblings or parents. However, occurrence of cases in clusters, seasonal variation, and very low risk of recurrence suggests an acquired trigger (such as infections) for the development of illness. Epigenetic mechanisms that modulate gene expression can plausibly explain the link between genetic and acquired predisposing factors in KD. Analysis of epigenetic factors can also be used to derive biomarkers for diagnosis and prognostication in KD. Moreover, epigenetic mechanisms can also help in pharmacogenomics with the development of targeted therapies. In this review, we analysed the available literature on epigenetic factors such as methylation, micro-RNAs, and long non-coding RNAs in KD and discuss how these mechanisms can help us better understand the disease pathogenesis and advance the development of new biomarkers in KD.